2021
DOI: 10.1123/ijatt.2020-0024
|View full text |Cite
|
Sign up to set email alerts
|

Parental Perceptions of the Importance and Effectiveness of Patient-Centered Care Delivery

Abstract: Integrative patient-centered care (PCC) models encompass all dimensions of the patient, including physical well-being, evidence-based shared decision making, and determinants of health as they relate to quality of life. The purpose of this study was to explore parental experiences with the principles of PCC, related to the healthcare of their dependent after interactions with a provider. Using an observational design, our results demonstrated that parents of adolescent athletes rated PCC concepts as “very impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 29 publications
3
9
0
Order By: Relevance
“…Seven of the eleven included studies are cross-sectional study designs [ 19 , 20 , 21 , 22 , 23 , 24 , 25 ], one study is a qualitative study [ 26 ], one is a case report [ 27 ], one study is a randomized prospective design [ 28 ], and one is a prospective cohort design [ 29 ]. Table 1 and Table 2 includes data extracted from these included studies.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Seven of the eleven included studies are cross-sectional study designs [ 19 , 20 , 21 , 22 , 23 , 24 , 25 ], one study is a qualitative study [ 26 ], one is a case report [ 27 ], one study is a randomized prospective design [ 28 ], and one is a prospective cohort design [ 29 ]. Table 1 and Table 2 includes data extracted from these included studies.…”
Section: Resultsmentioning
confidence: 99%
“…There were no differences reported among younger adolescents (10–14 years old) compared to older adolescents (15–18 years old), so results are representative of adolescent patients as a whole. The top two most important attributes to adolescents were shared decision making and understanding patients’ sports and goals [ 20 , 22 , 24 , 27 , 29 ]. Additionally, the highest valued physician characteristic from adolescent patients in a study by Beck et al, 2021 [ 29 ], was being a good listener and the lowest reported was “physician does not involve them in decision making”.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations